2021
DOI: 10.3390/pharmaceutics13071078
|View full text |Cite
|
Sign up to set email alerts
|

Novel Non-Congeneric Derivatives of the Choline Kinase Alpha Inhibitor ICL-CCIC-0019

Abstract: Choline kinase alpha (CHKA) is a promising target for the development of cancer therapeutics. We have previously reported ICL-CCIC-0019, a potent CHKA inhibitor with high cellular activity but with some unfavorable pharmacological properties. In this work, we present an active analogue of ICL-CCIC-0019 bearing a piperazine handle (CK146) to facilitate further structural elaboration of the pharmacophore and thus improve the biological profile. Two different strategies were evaluated in this study: (1) a prodrug… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 54 publications
0
1
0
Order By: Relevance
“…Consistently, shRNA-mediated in vivo depletion of CHKA decreases the growth of prostate tumor xenografts [ 5 ]. Very efficient CHKA inhibitors have been developed and considered in clinical trials, however, they have manifested elevated toxicity, as reported in [ 7 , 15 , 16 , 17 ]. Hence, alternative strategies should be considered.…”
Section: Introductionmentioning
confidence: 99%
“…Consistently, shRNA-mediated in vivo depletion of CHKA decreases the growth of prostate tumor xenografts [ 5 ]. Very efficient CHKA inhibitors have been developed and considered in clinical trials, however, they have manifested elevated toxicity, as reported in [ 7 , 15 , 16 , 17 ]. Hence, alternative strategies should be considered.…”
Section: Introductionmentioning
confidence: 99%